A Response to the Use of Goat Manure and Swallow Manure Fertilize Planting Media on Cocoa Plant Growtha - Thamrin, Syahruni; Syahid, Adi; Junaedi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2025)
Cocoa production is closely related to the implementation of cultivation techniques and seedling quality. Various efforts have been made to obtain the expected seedlings, including by providing nutrients in the planting media according to the needs of the seedlings. The study aimed to determine the best planting media for cocoa seedling growth by applying fertilizer from goat manure and swallow droppings. The research was conducted from January to April 2024 in Tarengge Village, Wotu Subdistrict, East Luwu Regency, South Sulawesi Province. The research was conducted using a Randomized Group Design (RAK), with planting media treatment (K) consisting of four treatments, namely K0= soil (control), K1= soil+ goat manure (1:1), K2 = soil+ swallow manure (1:1), and K3 = soil + goat manure + swallow manure (1:1:1). The four treatments were repeated three times and each replication contained two polybag units, making a total of 24 experimental units. The growth parameters observed were: plant height, number of leaves, and stem diameter. The results of the research obtained were then tabulated and processed using the STAR application, then the results of the analysis of variance that had a real or very real effect on the parameters observed would be subjected to further tests of the Least Significant Difference (BNT). The results showed that the planting media mixture of soil, goat manure, and swallow manure (1:1:1) had a significant effect on the observed parameters. The results showed that the mixed planting medium of soil, goat manure, and swallow manure (1:1:1) produced a plant height of 18.33 cm, 8.66 leaves, and a stem diameter of 1.40 cm.